Performance of ‘William’s’ pear grafted onto three rootstocks - da Silveira Pasa, Mateus; Dutra Schmitz, Juliano; Fagundes da Rosa Júnior, Horacy; Külkamp de Souza, André Luiz; Barbosa Malgarim, Marcelo; de Mello-Farias, Paulo Celso (Revista Ceres, 2025)
Pears are the most imported fruit from Brazil and thus, being an important opportunity to Brazilian growers. However, there are still some problems that restrict pear production, such as the lack of suitable rootstocks. The aim of this study was to assess growth, yield efficiency and fruit quality of ‘William’s’ pear grafted on quinces ‘Champion’ and ‘Melliforme’ and P. calleryana. The experiment was performed during 2009/2010 growing season at the Centro Agropecuário da Palma, FAEM/UFPel. The experimental design was a completely randomized block with three replications per treatment. The assessed parameters were trunk cross sectional area, shoot length, yield efficiency, number of fruit per tree, soluble solids, flesh firmness, fruit weight and fruit size. It was found that ‘William’s’ pear is more efficient and less vigorous when grafted on ‘Champion’ quince, thus being a potential scion x rootstock combination for commercial pear planting at medium densities. Moreover, fruit of trees grafted on quince rootstocks accumulated higher amount of soluble solids.